Research Thermal Fields in the Crystallization Process of Steel Cast Parts - Rostyslav Liutyi; Ivan Petryk; Volodymyr Mogylatenko; Vasyl Popovych; Halyna Shatska (Advances in Materials Science and Engineering)
In foundry production, the duration of metal crystallization of the cast part, as well as the distribution of the thermal field, are described by systems of analytical equations. There are a number of methods for modeling these processes, but their theoretical basis was formed at the end of the twentieth century, and it needs to be updated and clarified. Therefore, the aim of our work is to develop a new analytical method for researching the distribution of thermal fields in cast parts during crystallization. For the first time, on the basis of own analytical and thermophysical developments, it developed the analytical method for researching the thermal field of the casting during crystallization and cooling, which is based on establishing the kinetics of cooling of the casting surface in the foundry mold, the advancement of the crystallization front from the surface to the center of the casting, and the distribution of temperatures in the solid and liquid parts of the casting. The method is expressed in a number of analytical formulas, each of which describes the specific thermal process that occurs in the casting. The developed analytical method was used to research the crystallization of the casting in a one-time sand mold, using the example of researching the thermal field of the cast part made of carbon steel with 0.25% C, hollow cylindrical shape, with the wall thickness of 100 mm. The developed analytical method for researching the thermal fields of cast parts is the analytical basis for the refinement of applied computer programs for modeling crystallization and cooling processes in foundry production.